Regulation of Sucrose non-Fermenting Related Kinase 1 genes in Arabidopsis thaliana - Williams, Sarah P.; Rangarajan, Padma; Donahue, Janet L.; Hess, Jenna E.; Gillaspy, Glenda E. (Frontiers in Plant Science, 2014)
The Sucrose non-Fermenting Related Kinase 1 (SnRK1) proteins have been linked to regulation of energy and stress signaling in eukaryotes. In plants, there is a small SnRK1 gene family. While the SnRK1.1 gene has been well studied, the role other SnRK1 isoforms play in energy or stress signaling is less well understood. We used promoter:GUS analysis and found SnRK1.1 is broadly expressed, while SnRK1.2 is spatially restricted. SnRK1.2 is expressed most abundantly in hydathodes, at the base of leaf primordia, and in vascular tissues within both shoots and roots. We examined the impact that sugars have on SnRK1 gene expression and found that trehalose induces SnRK1.2 expression. Given that the SnRK1.1 and SnRK1.2 proteins are very similar at the amino acid level, we sought to address whether SnRK1.2 is capable of re-programming growth and development as has been seen previously with SnRK1.1 overexpression. While gain-of-function transgenic plants overexpressing two different isoforms of SnRK1.1 flower late as seen previously in other SnRK1.1 overexpressors, SnRK1.2 overexpressors flower early. In addition, SnRK1.2 overexpressors have increased leaf size and rosette diameter during early development, which is the opposite of SnRK1.1 overexpressors. We also investigated whether SnRK1.2 was localized to similar subcellular compartments as SnRK1.1, and found that both accumulate in the nucleus and cytoplasm in transient expression assays. In addition, we found SnRK1.1 accumulates in small puncta that appear after a mechanical wounding stress. Together, these data suggest key differences in regulation of the SnRK1.1 and SnRK1.2 genes in plants, and highlights differences overexpression of each gene has on the development of Arabidopsis.